Assessing the main determinants of entrepreneurship in Portugal - Vanessa Figueiredo; Ana Oliveira Brochado (Tourism & Management Studies)
Without question, entrepreneurship is present in all spheres of our lives, especially in economic and social areas. This field is significant in the development of societies and is also considered a useful tool in promoting innovation and job creation in many countries. For this reason, it needs to be promoted as a central component of economic growth. As a result, the creation of new businesses or projects and the promotion of self-employment have been stimulated by public and private organisations. The goal of this research is to determine what triggers individuals to be actively involved in entrepreneurial activity in the initial phases, based on a survey by Global Entrepreneurship Monitor conducted in Portugal, in 2012. The results of this analysis revealed that early-stage entrepreneurial activity is associated with younger (25–34 years old) males, who have a medium to higher level of household income, as well as diplomas. They are self-employed, and they have loose ties to other entrepreneurs. They perceive themselves as possessing entrepreneurial skills and have a low level of perceived risk and a positive personal attitude towards individual innovation.